ANALISIS PANDEMI COVID-19 SEBAGAI DASAR TERJADINYA FORCE MAJEURE DALAM SUATU PERJANJIAN (STUDI KASUS PUTUSAN NOMOR 629/Pdt.G/2020/PN JKT.SEL) - Christopher Kendrick Adam; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2022)
Force Majeure is a situation in which makes the debtor in an agreement enter a forceful station that makes the debtor’sobligation becoming impossible or very dif icult to execute in which the debtor won’t be able to finish their obligationwithout suf ering great losses especially in a disaster. In this case the accused which is also the debtor in the agreementthat is related to the genesis of Force Majeure because of the many dif iculties relating to production that is caused byCOVID-19 Pandemic. The writer is researching matter related to the judge’s consideration in this case in which if theconsideration itself can be considered as Force Majeure in law using the research method of empirical legal research.The result of this research will be based from the writers opinion that the Judge’s consideration didn’t fully recognizefully the validity of proof from one of the party that participate in this case, because if the proof from all party has beenfully considered and recognized then it could be the case that relative Force Majeure can be applied in this case. Thewriter hope that judges in the future can fully consider all the proof from all party fairly.